Capitalising on Positive Work Events by Sharing them at Home. Issue 3 (28th November 2013) - Ilies, Remus; Keeney, Jessica; Goh, Zen W.
<x xml:space="preserve">Abstract</x> The authors integrate existing theory on work–family integration and interpersonal capitalisation on positive work events by examining the effects of sharing positive work events with one's spouse on employee life satisfaction. A field study was conducted with 131 employees of a large Midwestern university, who completed surveys online. Participants provided accounts of their most important positive event during the prior week and indicated whether they had shared this event with their spouse. They also retrospectively rated their positive affect and life satisfaction over the course of the study. Results based on hierarchical regression analysis indicated that having shared that event with one's spouse was positively associated with positive affect and life satisfaction after controlling for personality and event characteristics. These results were corroborated in a subsample of 99 employees whose spouses provided independent reports of whether the event was shared with them. This research reveals that sharing positive events with others has unique and significant contributions to positive affect and life satisfaction. More importantly, these findings show that the interpersonal act of sharing is effective when conducted cross‐domain: the act of sharing positive work events with family members increases positive affect and life satisfaction.